ANALISIS PENGARUH STORE ATMOSPHERE, HARGA, KUALITAS PELAYANAN, DAN KERAGAMAN PRODUK TERHADAP KEPUASAN KONSUMEN PADA CAFE & RESTO - Sunarso, Ratna Sari Nur Indah Safitri, Setyaningsih Sri Utami & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this study to determine the significance of the effect of storeatmosphere, price, service quality, and diversity of products to customer satisfaction.This study uses a survey conducted in Rumah Kopi Sragen Cafe & Resto. Sources ofdata in the form of primary data and secondary data. Data collection techniques withquestionnaires, interviews, and literature. The sampling technique uses accidentalsampling of 100 respondents. Data were analyzed using multiple linear regression, theclassical assumption test, t test, F test and test the coefficient of determination. Theresults of this study indicate that the store atmosphere significantly influence consumersatisfaction in Rumah Kopi Sragen Cafe & Resto, prices significantly influenceconsumer satisfaction in Rumah Kopi Sragen Cafe & Resto, service quality significantlyinfluence consumer satisfaction in Rumah Kopi Sragen Cafe & Resto, diversity productssignificantly influence consumer satisfaction in Rumah Kopi Sragen Cafe & Resto. Fourvariables contributed 54,3 percent.Keywords: store atmosphere, price, service quality, product diversity, consumersatisfaction.